PENGARUH TINGKAT PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT MENJADI ENTREPRENEUR PADA MAHASISWA (Studi kasus mahasiswa UBSI cabang Salemba 22 Jakarta) - Fajar Diah Astuti; Rawit Sartika; Panji Suratriadi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2020)
The Central Statistics Agency announced that the unemployment rate until August 2019 became 7.05 million people. Interference for young people with a college education background for diplomas from 2017-2019 rose 8.5%, for university graduates or graduates from 2017-2019 it rose to 25%. This situation should be a concern for students to create jobs by becoming an entrepreneur. The research method used is quantitative methods by conducting surveys and interviews and processing the data using SPSS 19. The results of data processing obtained correlation/relationship coefficient (R) = 0.949, and the coefficient of determination (R²) of R² = 0.901, it can be said the level of entrepreneurial knowledge 90.1% strongly influence students' interest in becoming entrepreneurs, the remaining 9.9% is influenced by other factors. And the simple regression equation results are Y = 0.517 + 0.486X, meaning that each addition of 1 (one) business will increase the amount of student interest in becoming an entrepreneur by 0.486. It can be said that the interest of students to become entrepreneurs is very strongly influenced by the level of entrepreneurial knowledge. Keywords: entrepreneurship knowledge, interest in becoming entrepreneurs